Observation of Undamped 3D Brownian Motion of Nanoparticles Using Liquid‐Cell Scanning Transmission Electron Microscopy. (6th May 2020) - Welling, Tom A. J.; Sadighikia, Sina; Watanabe, Kanako; Grau‐Carbonell, Albert; Bransen, Maarten; Nagao, Daisuke; van Blaaderen, Alfons; van Huis, Marijn A.
Abstract: In theory, liquid‐cell (scanning) transmission electron microscopy (LC(S)TEM) is the ideal method to measure 3D diffusion of nanoparticles (NPs) on a single particle level, beyond the capabilities of optical methods. However, particle diffusion experiments have been especially hard to explain in LC(S)TEM as the observed motion thus far has been slower than theoretical predictions by 3–8 orders of magnitude due to electron beam effects. Here, direct experimental evidence of undamped diffusion for two systems is shown; charge‐neutral 77 nm gold nanoparticles in glycerol and negatively charged 350 nm titania particles in glycerol carbonate. The high viscosities of the used media and a low electron dose rate allow observation of Brownian motion that is not significantly altered by the electron beam. The resulting diffusion coefficient agrees excellently with a theoretical value assuming free diffusion. It is confirmed that the particles are also moving in the direction parallel to the electron beam by simulating STEM images using Monte Carlo simulations. Simulations and experiments show blurring of the particles when these move out of focus. These results make clear that direct observation of 3D diffusion of NPs is possible, which is of critical importance for the study of interparticle interactions or in situ colloidal self‐assembly using LC(S)TEM. Abstract : In theory, liquid‐cell transmission electron microscopy is the ideal method to measure 3D diffusion of single nanoparticles. However, mobilities reported thus far are 3–8 orders of magnitude lower than expected. Here, direct experimental evidence of undamped Brownian diffusion for two systems is shown; charge‐neutral 77 nm gold nanoparticles in glycerol and negatively charged 350 nm titania particles in glycerol carbonate.